O assentamento Dezessete de Abril e seu projeto de escola integral para o campo - Vale, Samila Bernardi do (2011)
The present work has how I aim to investigate the implementation of the project of school of full time, in the school daily life of the EMEIF Leonnor Mendes from Clays. So, this one investigates if it proposes accompanying the development of this project and checking which type of education has been offered for the pupils who frequent it, which or which the conception of education is behind this project and finally, to check if this education has been contributing in the formation of these pupils. Due to the fact of the school to be located in the rural environment we look to discuss the necessity or not of an education special for the population of the field, from the discussion the rural Brazilian again , of the formulations that the social and intellectual movements tied to same carried out on a proposal of Education of the Field and of the conception of Marxist education. Embasados for these formulations about the reality of the rural way and of the education offered to this population looks to do an analysis of the project of education of full time of the EMEIF Leonnor Mendes from Clays, of like the children who study in this school they can be benefited, or not, by the project.